Balancing Transparency and Innovation in the Global Litigation Finance Market: A Qualitative Synthesis of Risks, Regulation, and Policy Debates - Novrizal; Ria Wulandari (International Journal of Business Law, Business Ethic, Business Comunication & Green Economics, 2026)
This qualitative literature review examines how global litigation finance markets manage the tension between transparency requirements and innovation dynamics. Drawing on academic scholarship, policy reports, court decisions, and industry analyses, the review synthesizes evidence on disclosure obligations, funder influence, national security concerns, and emerging regulatory models. Findings show that while transparency enhances judicial integrity and mitigates conflicts of interest, excessive disclosure may undermine commercial confidentiality and inhibit investment in complex claims. Across jurisdictions, regulatory debates converge on the need for proportionate, court directed mechanisms such as limited in camera disclosure, provenance checks, and funder conduct safeguards. The review concludes that transparency and innovation are not mutually exclusive; instead, balanced regulatory frameworks can preserve market efficiency while protecting due process values and preventing geopolitical misuse. The study highlights significant data gaps and calls for deeper empirical research to guide evidence based policy making.